2012
DOI: 10.1111/j.1742-7924.2012.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of community‐based case management by visiting nurses for low‐income patients with hypertension in South Korea

Abstract: This study serves as a baseline for visiting nurse-driven case management for low-income patients with hypertension. Its findings suggest that visiting nurse-driven case management targeting the self management of BP can foster improved BP control for newly diagnosed hypertensive patients in low-income populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…The qualifications nurses should have for delivering interventions was reported by Kim et al. () and So et al. ().…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The qualifications nurses should have for delivering interventions was reported by Kim et al. () and So et al. ().…”
Section: Resultsmentioning
confidence: 95%
“…Self‐management activities are important indicators of chronic illness control (Kim et al. ). Four studies reported changes in self‐management (Cho et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations